Disparities in Postoperative Therapy for Salivary Gland Adenoid Cystic Carcinomas - Cassidy, Richard J. (Laryngoscope, 2018)
OBJECTIVES: The patterns of care for salivary gland adenoid cystic carcinomas (ACC) is unknown. We sought to assess predictors of receiving postoperative radiation and/or chemotherapy for patients with non-metastatic, definitively resected ACC, as well as report unexpected nodal disease. METHODS: The National Cancer Data Base was queried for definitively resected non-metastatic ACC from 2004 to 2014. Logistic regression, Kaplan-Meier, and Cox proportional-hazard models were utilized. Propensity-score matched (PSM) analysis was employed to reduce confounding variables. RESULTS: 3,136 patients met entry criteria: 2,252 (71.8%) received postoperative radiation with 223 (7.4%) also receiving concurrent chemotherapy. Median follow up was 4.87 years. In cN0 patients, 7.4% had pN+ after elective neck dissection. Patients who lived closer to their treatment facility and had positive margins were more likely to receive postoperative radiation. Black patients and uninsured patients were less likely to receive radiation. Older age, male sex, advancing stage, and positive surgical margins were associated with worse OS. With limited follow-up, receipt of radiation or chemotherapy was not associated with overall survival (OS). CONCLUSION: Postoperative radiation was frequently given for resected ACC with a minority receiving chemotherapy. Black patients and uninsured patients were less likely to receive radiation. Postoperative radiation and/or chemotherapy had no association with OS but was given more frequently in more advanced disease, and our series is limited by short follow-up. The disparity findings for this rare disease need to be addressed in future studies.